2022
DOI: 10.1245/s10434-022-12126-7
|View full text |Cite
|
Sign up to set email alerts
|

No One-Size-Fits-All: Sexual Health Education Preferences in Patients with Breast Cancer

Abstract: Background Using explanatory mixed methods, we characterize the education that patients with breast cancer received about potential sexual health effects of treatment and explore preferences in format, content, and timing of education. Patients and Methods Adult patients with stage 0–IV breast cancer seen at an academic breast center during December 2020 were emailed questionnaires assessing sexual health symptoms experienced during treatment. Patients interested in fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…14,[19][20][21][22][23] In addition, research on women with early breast cancer indicated a strong preference for providers to ask about sexual health early and often by incorporating this into routine screening performed over the course of care. 24 All too often, however, health care providers and trainees do not feel adequately prepared to discuss sexual health concerns with patients; primary care providers and OB/GYN's cite a perception of a lack of effective therapies as a barrier to initiating assessment of sexual health concerns. More than half of OB/GYN residents in a recent survey were unable to describe the disorders of sexual function or list medications that affect sexual function.…”
Section: Sexual Health Concerns Among Adult Patients In Ob/ Gyn Practicementioning
confidence: 99%
See 1 more Smart Citation
“…14,[19][20][21][22][23] In addition, research on women with early breast cancer indicated a strong preference for providers to ask about sexual health early and often by incorporating this into routine screening performed over the course of care. 24 All too often, however, health care providers and trainees do not feel adequately prepared to discuss sexual health concerns with patients; primary care providers and OB/GYN's cite a perception of a lack of effective therapies as a barrier to initiating assessment of sexual health concerns. More than half of OB/GYN residents in a recent survey were unable to describe the disorders of sexual function or list medications that affect sexual function.…”
Section: Sexual Health Concerns Among Adult Patients In Ob/ Gyn Practicementioning
confidence: 99%
“…A proactive style, where the provider enquires about sexual functioning in the past, is “permission granting” to patients to discuss such problems in the future 14,19–23 . In addition, research on women with early breast cancer indicated a strong preference for providers to ask about sexual health early and often by incorporating this into routine screening performed over the course of care 24 …”
Section: Sexual Health Concerns Among Adult Patients In Ob/gyn Practicementioning
confidence: 99%
“…9 Additionally, we had papers exploring aspects of breast sensuality in survivors and sexual health education. 10,11 Lastly, we had several papers examining axillary response to neoadjuvant treatment in the age of tumor genomic testing supporting de-escalation of axillary surgery in situations where it may not impact adjuvant treatment decisions. 12,13 Despite these turbulent times during the COVID-19 pandemic, the science of breast cancer surgical treatment continues as we study ways to refine our techniques and indications in the face of unforeseen challenges and improve surgical treatment for patients.…”
Section: Oral and Scientific Session Highlightsmentioning
confidence: 99%
“…Studies have shown that breast cancer patients want more sexual health information from their healthcare providers 10–12 . Patients prefer to have the information before their treatments so that they are able to prepare, adjust, and cope with the changes in their sexual health—as one of the patients in Huynh et al's study quoted, “more preventative than reactionary.” 7,13 While providers do not need to be sexual health experts to provide guidance, they may benefit from having the knowledge or tools to counsel patients effectively 9 . In this paper, we aim to share ways for providers to address sexual health concerns for breast cancer patients at different stages of the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Patients report that they would like information and counseling throughout their cancer experience. 7,13 Here, we provide four recommendations for all providers throughout care (Figure 1).…”
mentioning
confidence: 99%